Risk factors for hyperferritinemia secondary to red blood cell transfusions in pediatric cancer patients1. Issue 10 (17th June 2013) - Amid, Ali; Barrowman, Nick; Vijenthira, Abi; Lesser, Pat; Mandel, Karen; Ramphal, Raveena
Abstract Background Transfusion of packed red blood cells is common in pediatric cancer patients who receive chemotherapy. This study was done to identify characteristics of pediatric cancer patients at risk of hyperferritinemia secondary to frequent transfusions. Procedure In this retrospective chart review, all pediatric cancer patients who completed chemotherapy from January 2007 to January 2012 and had an assessment of serum ferritin 6 months after the end of treatment were included. Variables included: age, sex, type of cancer diagnosis, weight and body surface area (BSA) at the time of diagnosis, number of transfusions, total transfused volume (TTV), total transfused volume per body weight (TVPBW), and weight and BSA change from the time of diagnosis to the time of ferritin check. Results Of 109 eligible patients, 85 (78%) received transfusions. Sixteen patients (14.7%) had ferritin levels > 200 µg/L and four (3.7%) had ferritin levels > 1, 000 µg/L. Although age, weight and BSA at cancer diagnosis, number of transfusions and TVPBW were correlated with the level of ferritin, independent risk factors were TTV (range 1, 961–30, 090 ml in patients with hyperferritinemia, P < 0.001) and BSA change from the time of diagnosis to the time of ferritin check (range −0.15 to 0.31 m2 in patients with hyperferritinemia, P < 0.001). Increase in BSA was correlated with reduction of hyperferritinemia in follow‐up ferritin measurements (P = 0.049). Conclusions In addition to TTV, change in BSA is an independent predictor for the degree and possibly persistence of hyperferritinemia in pediatric cancer patients and should be considered in decisions to initiate interventions. Pediatr Blood Cancer 2013;60:1671–1675. © 2013 Wiley Periodicals, Inc.